ABA signalling promotes cell totipotency in the shoot apex of germinating embryos. (27th June 2021) - Chen, Baojian; Fiers, Martijn; Dekkers, Bas J W; Maas, Lena; van Esse, G Wilma; Angenent, Gerco C; Zhao, Yang; Boutilier, Kim
Abstract : Molecular–genetic analysis of Arabidopsis mutants revealed a novel role for abscisic acid in promoting auxin-induced somatic embryogenesis at three different levels: biosynthesis, signalling, and downstream transcription. Abstract: Somatic embryogenesis (SE) is a type of induced cell totipotency where embryos develop from vegetative tissues of the plant instead of from gamete fusion after fertilization. SE can be induced in vitro by exposing explants to growth regulators, such as the auxinic herbicide 2, 4-dichlorophenoxyacetic acid (2, 4-D). The plant hormone abscisic acid (ABA) has been proposed to be a downstream signalling component at the intersection between 2, 4-D- and stress-induced SE, but it is not known how these pathways interact to induce cell totipotency. Here we show that 2, 4-D-induced SE from the shoot apex of germinating Arabidopsis thaliana seeds is characterized by transcriptional maintenance of an ABA-dependent seed maturation pathway. Molecular–genetic analysis of Arabidopsis mutants revealed a role for ABA in promoting SE at three different levels: ABA biosynthesis, ABA receptor complex signalling, and ABA-mediated transcription, with essential roles for the ABSCISIC ACID INSENSITIVE 3 (ABI3) and ABI4 transcription factors. Our data suggest that the ability of mature Arabidopsis embryos to maintain the ABA seed maturation environment is an important first step in establishing competence for auxin-induced cell totipotency. This finding provides further support for the role of ABA in directing processes other than abiotic stress response.